Unlocking further potential in the national cohort study through comparability with the German socio-economic panel - Hannes Kröger; Jürgen Schupp; Johann Behrens (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Background: The National Cohort (Nationale Kohorte = NaKo) will be one of the largest cohort studies in Europe to include intensive physical examinations and extensive information about the socio-demographic background and behavior of the subjects. However, regional selectivity of the study and potential learning effects due to the panel structure of the data present challenges for researchers using it. Methods: We discuss the two problems and show how they might lead to potential biases when trying to obtain results from the National Cohort that are representative for the total population of Germany. We suggest that the long-running German Socio-Economic Panel Study (SOEP) should be used as a reference data set for population means and as a control sample for detection of learning effects (panel effects) induced by information about the results of individual medical examinations. Results: We present a wide range of topics and indicators which are available in both the German Socio-Economic Panel Study (SOEP) and the National Cohort (NaKo). These items can be harmonized to make the datasets comparable. The range of topics that overlap between SOEP and NaKo include socio-demographic variables, general indicators, socio-psychological environment, and to a limited extent biomarkers. Conclusion: Harmonizing certain survey item batteries from the NaKo to the SOEP standard can yield a great deal of additional research potential. This holds true both for researchers mainly interested in the NaKo data and for those mainly interested in the SOEP.
Keywords: 330; National Cohort; NaKo; German Socio-Economic Panel Study; SOEP; survey; study design; health surveys